Inhibition of S. aureus Infection of Human Umbilical Vein Endothelial Cells (HUVECs) by Trehalose‐ and Glucose‐Functionalized Gold Nanoparticles. (9th September 2021) - Li, Yimeng; Ariotti, Nicholas; Aghaei, Behnaz; Pandzic, Elvis; Ganda, Sylvia; Willcox, Mark; Sanchez‐Felix, Manuel; Stenzel, Martina
Abstract: Microbial adhesion to host cells represents the initial step in the infection process. Several methods have been explored to inhibit microbial adhesion including the use of glycopolymers based on mannose, galactose, sialic acid and glucose. These sugar receptors are, however, abundant in the body, and are not unique to bacteria. Trehalose, in contrast, is a unique disaccharide that is widely expressed by microbes. This carbohydrate has not yet been explored as an anti‐adhesive agent. Herein, gold nanoparticles (AuNPs) coated with trehalose‐based polymers were prepared and compared to glucose‐functionalized AuNPs and examined for their ability to prevent binding to endothelial cells. Acting as anti‐adhesive agents, trehalose‐functionalized NPs decreased the binding of S. aureus to HUVECs, while outperforming the control NPs. Microscopy revealed that trehalose‐coated NPs bound strongly to S. aureus compared to the controls. In conclusion, nanoparticles based on trehalose could be a non‐toxic alternative to inhibit S. aureus infection. Abstract : Due to increased resistance against antibiotics, the fight against bacteria is becoming increasingly difficult. Here, we used a sugar that is unique to the bacteria metabolism, trehalose, and prepared trehalose‐based polymer‐coated gold nanoparticles. These nanoparticles were shown to inhibit the infection of healthy cells by S. aureus and could serve as a non‐toxic alternative to prevent adhesion of certain bacteria.